1995
DOI: 10.1016/0042-6989(94)00221-7
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the role of the retinal dopamine/melatonin system in experimental refractive errors in chickens

Abstract: We have found that development of both deprivation-induced and lens-induced refractive errors in chickens implicates changes of the diurnal growth rhythms in the eye (Fig. 1). Because the major diurnal oscillator in the eye is expressed by the retinal dopamine/melatonin system, effects of drugs were studied that change retinal dopamine and/or serotonin levels. Vehicle-injected and drug-injected eyes treated with either translucent occluders or lenses were compared to focus on visual growth mechanisms. Retinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
110
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 153 publications
(119 citation statements)
references
References 34 publications
8
110
1
Order By: Relevance
“…3 Intravitreal injection of the D1R antagonist SCH 23390 enhanced FDM development in chickens. 49 Similarly, preliminary studies indicated the D1R agonist SKF 38393 inhibited FDM, whereas the D1R antagonist SCH 39166 enhanced FDM in mice (Zhou X, et al IOVS 2014;55:ARVO E-Abstract 3038). 30 However, other studies in chickens and tree shrews found that the development of FDM was not affected by intravitreal injection of the D1R antagonist SCH 23390.…”
Section: D1r-dependent Mechanism Of Apomorphine In Myopiamentioning
confidence: 99%
“…3 Intravitreal injection of the D1R antagonist SCH 23390 enhanced FDM development in chickens. 49 Similarly, preliminary studies indicated the D1R agonist SKF 38393 inhibited FDM, whereas the D1R antagonist SCH 39166 enhanced FDM in mice (Zhou X, et al IOVS 2014;55:ARVO E-Abstract 3038). 30 However, other studies in chickens and tree shrews found that the development of FDM was not affected by intravitreal injection of the D1R antagonist SCH 23390.…”
Section: D1r-dependent Mechanism Of Apomorphine In Myopiamentioning
confidence: 99%
“…Both D1R and D2R are implicated in refractive development. 22,23 A large body of experimental evidence supports the specific involvement of D2R in myopia development. [24][25][26] However, it is less clear whether or not D1R is involved in myopia development.…”
mentioning
confidence: 99%
“…Previously identified D1R involvement is based on pharmacology studies with chicken models of myopia. 24,25,27 For example, a D1R agonist SKF38393 inhibited FDM, 28 while a D1R antagonist, SCH 23390, enhanced this response 22 and inhibited the ameliorating effects of periods of clear vision on lens-induced myopia in chicks. 29 Similarly, a D1R antagonist SCH23390 enhanced progression of naturally occurring myopia while a D1R agonist SKF38393 inhibited it in albino guinea pigs.…”
mentioning
confidence: 99%
“…While diurnal retinal melatonin rhythms appear unaffected during form-deprivation (Hoffmann and Schaeffel 1996), the intra-vitreal injection of melatonin at relatively high doses (1000 g) increases the level of form-deprivation myopia induced in the chick (Schaeffel, Bartmann et al 1995;Hoffmann and Schaeffel 1996). Although retinal melatonin content was sampled twice a day (day and night) during monocular occlusion, and an expected diurnal variation in melatonin was found, no significant difference was found between the occluded and non-occluded eyes (Hoffmann and Schaeffel 1996).…”
Section: Melatoninmentioning
confidence: 99%